2003
DOI: 10.1073/pnas.2135413100
|View full text |Cite
|
Sign up to set email alerts
|

A plant virus replication system to assay the formation of RNA pseudotriloop motifs in RNA–protein interactions

Abstract: A pseudotriloop is formed by transloop base pairing between the first (5 ) and the fifth nucleotide in a hexanucleotide RNA loop (''hexaloop'') to subtend a triloop of nucleotides 2-4. This structure has been found in hairpins involved in the regulation of iron metabolism in mammalian cells and in transcription of plant virus subgenomic RNA. Several hexaloop hairpins, including HIV-transactivation-responsive element and hepatitis B virus , potentially adopt a pseudotriloop conformation. Here we show that an RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The HIV-1 TAR hairpin has been studied using NMR by others before, but in these cases the CG cross-loop resonance was also not observed (Jaeger and Tinoco 1993;Aboul-Ela et al 1996;Dethoff et al 2008Dethoff et al , 2012 although there is functional data to support its presence (Haasnoot et al 2003;Kulinski et al 2003). Our NMR data also showed no indication of a cross-loop base pair in tHIV and we ascribe this to the presence of an A-bulge and loop-closing CG base pair.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…The HIV-1 TAR hairpin has been studied using NMR by others before, but in these cases the CG cross-loop resonance was also not observed (Jaeger and Tinoco 1993;Aboul-Ela et al 1996;Dethoff et al 2008Dethoff et al , 2012 although there is functional data to support its presence (Haasnoot et al 2003;Kulinski et al 2003). Our NMR data also showed no indication of a cross-loop base pair in tHIV and we ascribe this to the presence of an A-bulge and loop-closing CG base pair.…”
Section: Discussionmentioning
confidence: 46%
“…We investigated the existence and thermodynamic stability of several PTL structures derived from various viral sources, including the HBV ɛ and HIV-1 TAR loops, and two postulated candidate PTLs: a stem-loop from a spumaretrovirus (HFV) and a bacterial hairpin involved in regulation of pyrimidine synthesis, pyrR (Haasnoot et al 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, BMV does not differ from the related alfalfa mosaic virus (AMV), for which it has been shown that the genomic promoter could substitute the subgenomic promoter in vitro and in vivo (Olsthoorn et al 2004). Interestingly, the AMV promoters for sgRNA and gRNA synthesis form a hairpin with a regular triloop but can be functionally replaced by hairpins with a pseudo-triloop, like HBV e (Flodell et al 2002(Flodell et al , 2006Haasnoot et al 2003), HIV-1 TAR (Haasnoot et al 2003) and the BMV subgenomic promoter (RCL Olsthoorn, unpubl. ).…”
Section: Discussionmentioning
confidence: 99%
“…The triloop motif is particularly interesting due to its major role in a variety of organisms and pathways, for instance, in the promotion of some virus replication (Huang et al 2001;Olsthoorn and Bol 2002), viral synthesis (Haasnoot et al 2003), and iron response (McCallum and Pardi 2003). Furthermore, a previous triloop study revealed an important structural diversity (Lee et al 2003), making this motif an ideal candidate for a base interaction characterization.…”
Section: Introductionmentioning
confidence: 99%